Cryopreserved Placental Derivatives Increase Survival of Mice With Cyclophosphamide-Induced Ovarian Failure - Prokopіuk, Volodymyr; Shevchenko, Mariіa; Kaverinska, Anna; Mykhalchuk , Tetyana; Prokopіuk, Olga (Problems of Cryobiology and Cryomedicine, 2023)
Probl Cryobiol Cryomed 2023; 33(1):059–063